MEDICAL IMAGE ANALYSIS PLATFORM - ZAHARI, MADIHA (Universiti Teknologi Petronas, 2006)
Medical imaging techniques are importance nowadays since it is beneficial in medical diagnosis especially for patient in cancer or internal problem. The most known imaging techniques are Magnetic Resonance Imaging (MRI) and Computerized Tomography (CT). The problem faced when using both techniques is the time consuming during the process of data acquiring. This project is to develop an algorithm to reduce the time consumptions in analyzing the images. This project can be used not only for medical application but also for biomedical research. By using statistical analysis approach, first order statistical algorithm and second order statistical algorithm focused on NGTDM are developed. The Graphical User interfaced also developed where all the designed steps are performed by using MATLAB. The results of analysis can be further used to analyze medical images and classify there images for medical diagnosis. From the results, it shows that the statistical analysis has potential to analyze the medical images and can be used as the first step in detecting any sign of disease. The accuracy of the analysis can be improved by conducting the analysis by using real medical images. v